Carbon Tax in Indonesia as a Fiscal Instrument and Climate Justice in Supporting the Green Economy: A Literature Review - Permata Brillyana Hardini; Haula Rosdiana (PT. Publikasiku Academic Solution, 2025)
The carbon tax is a fiscal and environmental policy instrument designed to reduce greenhouse gas (GHG) emissions through a carbon emissions pricing mechanism. This study examines carbon tax policy as both a fiscal tool and an instrument of climate justice in developing countries, focusing on Indonesia. Using a qualitative approach through literature analysis, this research assesses policy dynamics, economic-environmental co-benefits, and implementation challenges of carbon taxation in Indonesia. Findings indicate that carbon taxation significantly accelerates green economy transition by stimulating clean energy investment and augmenting fiscal revenue. However, effectiveness hinges on inclusive policy design, institutional readiness, and compensatory mechanisms for vulnerable populations. In Indonesia, under Undang-Undang Harmonisasi Peraturan Perpajakan (UU HPP) Law No. 7 of 2021, carbon tax implementation faces delays with uncertain deployment by 2025. This study underscores the necessity of integrating carbon taxation with social protection frameworks to mitigate regressive impacts and ensure equitable low-carbon energy transitions.